2007
DOI: 10.1080/10715760601169679
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticle is a useful scavenger of superoxide anion and hydrogen peroxide

Abstract: Bimetallic nanoparticles consisting of gold and platinum were prepared by a citrate reduction method and complementarily stabilized with pectin (CP-Au/Pt). The percent mole ratio of platinum was varied from 0 to 100%. The CP-Au/Pt were alloy-structured. They were well dispersed in water. The average diameter of platinum nanoparticles (CP-Pt) was 4.7 +/- 1.5 nm. Hydrogen peroxide (H(2)O(2)) was quenched by CP-Au/Pt consisting of more than 50% platinum whereas superoxide anion radical (O(2)(-)) was quenched by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(227 citation statements)
references
References 38 publications
7
218
2
Order By: Relevance
“…Antioxidant therapy is therefore considered an effective medical treatment for aging. It has been shown that nano-Pt can function as a strong, stable reducing catalyst that efficiently quenches ROS (16). Since the use of platinum as a food additive has been approved, commercial products supplemented with nano-Pt have been marketed in Japan as antioxidants (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant therapy is therefore considered an effective medical treatment for aging. It has been shown that nano-Pt can function as a strong, stable reducing catalyst that efficiently quenches ROS (16). Since the use of platinum as a food additive has been approved, commercial products supplemented with nano-Pt have been marketed in Japan as antioxidants (17).…”
Section: Discussionmentioning
confidence: 99%
“…Platinum nanoparticles (nano-Pt) have attracted attention in recent years due to the fact that they have been shown to scavenge ROS persistently and catalytically (16). Nano-Pt are colloids of nano-sized particles of platinum, which are added to health foods or cosmetics due to their antioxidation and anti-aging properties (17).…”
Section: Introductionmentioning
confidence: 99%
“…The dismutation catalysis takes place by making use of the Os VIII =Os VII redox couple: Os VIII is reduced by superoxide with a bimolecular rate constant of k ¼ 2.6Â10 9 M À1 s À1 , and the resulting Os VII is oxidized back to Os VIII by superoxide, with a bimolecular rate constant of 1.0Â10 9 M À1 s À1 . Finally, the potential of Pt nanoparticles as SOD mimics has been reported in extending the life span of Caenorhabditis elegans (168,173). The effect at 0.5 mM only, but lack of it at 0.1 and 1 mM concentrations, raises concerns.…”
Section: Other Compoundsmentioning
confidence: 99%
“…Recent studies have demonstrated that metal nanoparticles are potential antioxidants. Bimetallic nanoparticles consisting of gold and platinum are effective in quenching reactive oxygen species (ROS), including hydrogen peroxide (H 2 O 2 ) and the superoxide anion radical (O 2 À ), in a dose-dependent manner, 4) and gold nanoparticles enhance the antioxidant activity of vitamin E. 5) In addition nanoparticles of gold and platinum have been found to catalyze oxidation of NADH to NAD. 6,7) ROS have been implicated in bone metabolism.…”
Section: Gold Nanoparticles Inhibited the Receptor Activator Of Nuclementioning
confidence: 99%